THE MAIN FEATURES OF ICT IN DEVELOPING SPEECH COMPETENCY (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
. this article gives information about improving speech competency through information and communication technologies in Universities. In addition, it provides several feasible methods in enhancing speech competency as well as brings approaches and ideas from prominent pedagogues.